A New Family of q-Supercongruences Modulo the Fourth Power of a Cyclotomic Polynomial - Guo, Victor J. W.; Schlosser, Michael J. (Resultate der Mathematik, 2020)
We establish a new family of q -supercongruences modulo the fourth power of a cyclotomic polynomial, and give several related results. Our main ingredients are q -microscoping and the Chinese remainder theorem for polynomials.